Lethal violence and religion: institutional and denominational effects on homicide and suicides in US counties - Robinson, Bryan K. (Criminal justice: recent scholarship, 2015)
Lethal violence in the United States -- The integrated model of lethal violence -- Religion and lethal violence rates -- Data and methods -- Results for the institutional effects model -- Results for the denominational effects model -- Conclusions